PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASI Studi pada Guru di SMP Negeri Se-Kawedanan Tayu Kabupaten Pati (Students' Journal of Economic and Management, 2013)
The purpose of this study was to analyse, experimentally, the relationships between principal leadership and work motivation to teacher performance with organizational commitments as intervening variable. Participants compriseed 150 teachers having educational certificate from the whole Kawedanan Tayu Pati region. With characteristics: min 30 years old, min S1 degree, and work duration min 5 years. The results are the first hypothesis (H1) “Principal leadership has positive and significant effect on organizational commitment, it means the better principal leadership will increase organizational commitment”. The second hypothesis (H2) “Work motivation doesn’t influence organizational commitment, it means the motivation given by teachers doesn’t increase organizational commitment”. The third hypothesis (H3) “Principal leadership has positive and significant impact on teacher performance, it means the better principal leadership will increase teacher performance”. The fourth hypothesis (H4) “Work motivation has positive and significant on teacher performance, it means the better work motivation will increase  teacher performance”. The fifth hypothesis (H5) “Organizational commitment has positive and significant impact on teacher performance, it means the better organizational commitment will increase teacher performance”. Key words: Principal leadership, work motivation, organizational commitment, and teacher performance.